The Honest Girl - Nze, Uchenna (Literamed Publications Nigeria Limited, 2010)
Amara starts out as a very greedy little girl who takes more than her own fair share of food, snacks and anything shared amongst her and others.However, she has a nightmare and her father narrates a story that transforms her into a responsible and honest young man.
Keywords: Adventure; Change; Juvenile Fiction